Analisis Lagu Pop Sunda “Jang” dan Relevansinya terhadap Layanan bimbingan dan konseling - Sutirna, Sutirna (Quanta : Jurnal Kajian Bimbingan dan Konseling dalam Pendidikan, 2024)
English: The purpose of this study is to provide information on the form of guidance and counseling services through the Sundanese pop song "JANG" as a medium for individual or personal guidance in order to live life and life in the present and future. The research instrument is in the form of song lyrics and comments from the public who listen, while the analysis of the results is seen from the meaning of the song which is described through the relationship with guidance and counseling services and the content of comments from song listeners via the YouTube channel. The results of this research study concluded that the Sundanese pop song "Jang" is very significant to be used as advice for students, college students, and the community as a reference in carrying out daily life. The implications of this research can be used to provide personal strengthening of learners, students, and society in living life and daily life for and materials for providing guidance and counseling services for teachers and lecturers. Indonesia: Tujuan penelitian ini ingin menginformasikan bentuk layanan bimbingan dan konseling malalui lagu pop sunda “JANG” sebagai media bimbingan individu atau pribadi guna menjalani hidup dan kehidupan masa kini dan mendatang. Instrumen penelitian ini berupa lirik lagu dan komentar dari masyarakat yang mendengarkan sedangkan analisis hasil di lihat dari pengertian lagu yang didiskripsikan melalui keterkaitan dengan layanan bimbingan dan konseling serta isi komentar para pendengar lagu melalui chanel youtube. Hasil kajian penelitian ini disimpulkan bahwa lagu pop sunda “Jang” sangat signifikan untuk dijadikan sebagai nasihat bagi para peserta didik, mahasiswa, dan masyarakat sebagai acuan dalam menjalankan kehidupan sehari-hari. Implikasi dari penelitian ini dapat dijadikan untuk memberikan penguatan pribadi peserta didik, mahasiswa, dan masyarakat dalam menjalani hidup dan kehidupan sehari-hari bagi  dan bahan memberikan layanan bimbingan dan konseling Guru dan Dosen